Correction: Ou et al. Autonomous Navigation by Mobile Robot with Sensor Fusion Based on Deep Reinforcement Learning. Sensors 2024, 24, 3895 - Yang Ou; Yiyi Cai; Youming Sun; Tuanfa Qin (Sensors)
There were errors in the original publication [...]